Research on design and applications of multistable mechanical metamaterial structures with high fatigue resistance - Song Gao; Meiling Zhang; Lang Yu; Jinkui Chu; Jianwei Sun; Luquan Ren (Engineering Structures, 2026)

Rapid Detection of Spring Viremia of Carp Virus ( SVCV ) Using RAA ‐ CRISPR /Cas12a - Xiaoyang Li; Aoqing Zhang; Yingying Li; Yingying Wang; Hao Zheng; Defeng Zhang; Yan Ren; Xubing Mo; Yuting Deng; Junyu Luo; Meiling Yu; Bo Chen; et al. (Journal of Fish Diseases, 2026)
Spring viremia of carp virus (SVCV), that can infect cyprinoid and koi causing an acute hemorrhagic symptom, with a feature of widespread epidemic, which poses a severe threat to the global aquaculture industry. Given the absence of specific effective medicine or vaccines, the early, accurate diagnosis is critical in the disease prevention. Many SVCV detection methods have been established, but most require specialized equipment and skilled operators, which limits their field application. In this study, we established a recombinase‐mediated isothermal amplification (RAA) in conjunction with the CRISPR/Cas12a system targeting the screened conserved region of the G gene in the genome to identify SVCV. The optimal combination of the primer pairs and crRNA was screened via the fluorescence intensity. In addition, the test exhibited high sensitivity and specificity, which could detect at the limit of 1.243 × 10 1 copies/μL and show no cross‐reactivity with other common freshwater fish pathogens. Furthermore, the result could be visible by excitation of fluorophores by blue light at 39°C within 30 min. The integrated method combines the advantages of RAA and CRISPR‐based signal transduction, offering a diagnosis project in resource‐limited aquaculture environments and a field‐applicable early warning of SVCV.

Explaining the spatial heterogeneity in soil–rice yield interactions via a hybrid interpretable machine learning and spatial analysis framework - Meiling Sheng; Xufeng Fei; Zhaohan Lou; Mingtao Xiang; Zhouqiao Ren; Xiaonan Lv; Rui Xiao (Journal of Environmental Management, 2026)

Preliminary study on targeted therapy of breast cancer using tumor cell membrane-coated dual-loaded liposomes based on chemo-photothermal synergistic effects - Yuwei Wang; Shuchao Pang; Yun Lu; Xialin Guo; Chanlian Li; Meiling Chen; Xiaoliang Ren (Drug Delivery and Translational Research, 2026)

Analysis of the spatiotemporal evolution and determinants of cultivated land quality under a hybrid-driven framework integrating multiple machine learning and geostatistical approaches - Meiling Sheng; Zhaohan Lou; Mingtao Xiang; Rui Xiao; Zhouqiao Ren; Xiaonan Lv; Xufeng Fei (Stochastic Environmental Research and Risk Assessment, 2026)

Spatiotemporal changes of soil organic carbon in intensive croplands over three decades: Emerging role of farmland utilization shifts - Mingtao Xiang; Xiaojia Chen; Songchao Chen; Chunyan Wu; Meiling Sheng; Zhouqiao Ren; Wanzhu Ma; Ming Ming; Xunfei Deng; Yu Zhan (Soil and Tillage Research, 2025)

Patterns and Influencing Mechanism of Plant Species Richness of Carex-dominated Wetlands in China - Jingci Meng; Guodong Wang; Yue Guo; Meiling Zhao; Nanlin Hu; Yusong Yuan; Yantong Zhao; Qi Chen; Zhibin Ren; Bo Liu; Ming Jiang (Chinese Geographical Science, 2025)

Estimating the spatial distribution and exploring the factors influencing cultivated land quality through a hybrid random forest and Bayesian maximum entropy model - Xufeng Fei; Zhaohan Lou; Meiling Sheng; Mingtao Xiang; Rui Xiao; Zhouqiao Ren; Xiaonan Lv (Environmental Research, 2025)

Self-assembled mogroside v nanomicelle system improves oral bioavailability of the magnolol - Chengzhi Liu; Lingyi Ren; Niu Liu; Mengchu Niu; Yifei Xiang; Xianhua Wu; Changhua Lin; Zhengmin Liang; Meiling Yu; Jiakang He (Food Chemistry, 2025)

Tamoxifen regulates ferroptosis of hepatocytes by targeting SLC1A5 to activate hepatic stellate cells and liver fibrosis - Sha Shi; Meiling Zhang; Chengkai Zhu; Shanhao Zhu; Jie Yu; Qi Sui; Jiaqi Xu; Juan Ren; Jingnan Zhang; Peng Chen; Yi Zhang (Chemico-Biological Interactions, 2025)

Exploring the spatio-temporal dynamics and driving mechanisms of toxic metal pollution in soil using a hybrid machine learning-based model - Mingtao Xiang; Zhaohan Lou; Meiling Sheng; Zhouqiao Ren; Rui Xiao; Xufeng Fei; Xiaonan Lv (Journal of Environmental Chemical Engineering, 2025)

Methyltransferase HsdM Regulates the Pathogenicity of Streptococcus agalactiae to Nile Tilapia (Oreochromis niloticus) - Dongdong Jiang; Bei Wang; Yan Ren; Xubing Mo; Meiling Yu; Defeng Zhang (Fishes, 2025)
DNA methylation is a critical mechanism for regulating gene expression in bacteria and plays an essential role in bacterial pathogenesis. A mutant, WC1535ΔhsdM, lacking hsdM encoding a DNA methyltransferase was constructed using homologous recombination technology. The growth, hemolytic activity, and capsule formation of the mutant were analyzed. The dynamic distribution of the wild-type (WT) and mutant strains in tilapia tissues after artificial infection was determined. The adhesion, invasion, anti-phagocytic, and whole-blood survival abilities of the WT and mutant strains were analyzed. Tilapia were intraperitoneally injected with the WT or mutant strains, and the LD50 values were determined. The expression levels of the immune-related genes in tilapia were analyzed by qRT-PCR. The mutant showed faster growth during the logarithmic growth period (5–10 h) and lower hemolytic activity than the WT strain. Mutant loads in tilapia tissues were significantly lower than those of the WT strain. Mutant strain adhesion to epithelial cells was significantly reduced, it was more easily engulfed by macrophages, and it had decreased intracellular survival. The LD50 of the mutant was 2.06 times higher than that of the WT strain, indicating decreased pathogenicity. Expression levels of immune-related genes IL-1β, IL-6, IFN-γ, and TNF-α in tilapia induced by the mutant were lower than those by the WT strain. In conclusion, the WC1535ΔhsdM mutant exhibited an increased growth rate and decreased hemolytic activity, tissue colonization, and pathogenicity, indicating that HsdM could regulate S. agalactiae growth and pathogenicity. This study provides new insights into the pathogenesis of piscine S. agalactiae.

A lightweight fine-grained pelagic fish recognition algorithm based on object detection - Weiyu Ren; Dongfan Shi; Yifan Chen; Liming Song; Qingsong Hu; Meiling Wang (Aquaculture International, 2025)

Dynamic planning of crowd evacuation path for metro station based on Dynamic Avoid Smoke A-Star algorithm - Songtao Zuo; Zhanli Mao; Chuangang Fan; Xin Chen; Meiling Gong; Jianxing Ren; Xiaoxiao Fan; Yongnan Guo (Tunnelling and Underground Space Technology, 2024)

Biochar decreases cadmium uptake in indica and japonica rice (Oryza sativa L.): Roles of soil properties, iron plaque, cadmium transporter genes and rhizobacteria - Meiling Xu; Meiling Ren; Yu Yao; Qi Liu; Jing Che; Xiaozhi Wang; Qiao Xu (Journal of Hazardous Materials, 2024)

Optimization of flavonoids extracted from hawthorn （Crataegus pinnatifida） by ultrasonic-assisted deep eutectic solvent - Xiaojing Sun; Meiling Fu; Shihao Lou; Dandan Li; Xue Han; Shan Gao; Jianhua Xiu; Junfeng Wang; Yuanyuan Ren (Food Bioscience, 2024)

Different “nongrain” activities affect the accumulation of heavy metals and their source-oriented health risks on cultivated lands - Xufeng Fei; Zhaohan Lou; Meiling Sheng; Xiaonan Lv; Zhouqiao Ren; Rui Xiao (Environmental Research, 2024)

Quantitative heterogeneous source apportionment of toxic metals through a hybrid method in spatial random fields - Xufeng Fei; Zhaohan Lou; Meiling Sheng; Lv Xiaonan; Zhouqiao Ren; Rui Xiao (Journal of Hazardous Materials, 2024)

Synthesis of MnOOH-hydroxyapatite nanowires for degradation of tetracycline - Shenglan Zhao; Meiling Zhou; Jiarui Ren; Yaping Zhang; Yufeng He; Rongmin Wang (Journal of Environmental Chemical Engineering, 2023)

Processing toxic metal source proxies appropriately for better spatial heterogeneity source apportionment - Meiling Sheng; Xufeng Fei; Zhaohan Lou; Rui Xiao; Zhouqiao Ren; Xiaonan Lv (Science of The Total Environment, 2023)

Dorsal and ventral fronto-amygdala networks underlie risky decision-making in age-related cognitive decline - Ping Ren; Manxiu Ma; Yuchuan Zhuang; Jiayin Huang; Meiling Tan; Donghui Wu; Guozhi Luo (GeroScience, 2023)
Older adults often have difficulty in making decisions under uncertainty, increasing the risk of financial exploitation. However, it is still under investigation about the extent to which cognitive decline influences risky decision-making and the underlying neural correlates. We hypothesized that the individual differences of risk-taking behavior depend on cognitive integrity, in which the dorsal and ventral fronto-amygdala connectivity would play dissociable roles. In the current study, thirty-six young and 51 older adults were tested with the Iowa gambling task combing resting-state and task-related functional magnetic resonance imaging. The results showed significant changes in behaviors and the fronto-amygdala network in older adults relative to young adults. More importantly, age-effect on risk-taking behaviors was remarkably different in cognitively normal and impaired older adults. In resting-state analysis, task performance was positively correlated with the ventral fronto-amygdala connectivity and negatively correlated with the dorsal fronto-amygdala connectivity in cognitively impaired older adults, compared with cognitively normal individuals. Furthermore, task-related analysis confirmed the relationships between dorsal/ventral fronto-amygdala network and risk-taking behaviors depending on cognitive integrity. These findings indicate that the fronto-amygdala network is crucial for understanding altered risky decision-making in aging, suggesting dissociable contributions of the dorsal and ventral pathways in the context of cognitive decline.

Study on optimization of shelter locations and evacuation routes of gas leakage accidents in chemical industrial park - Di Zhang; Zhanli Mao; Meiling Gong; Jianxing Ren; Songtao Zuo; Xin Chen (Process Safety and Environmental Protection, 2023)

Analysis of seismic escape accessibility and risk in old community with unreinforced masonry buildings - Meiling Xiao; Jianbin Xie; Cuilin Liu; Haiyan Zhu; Yong Zhu; Yujie Fu; Jun Ren (Stochastic Environmental Research and Risk Assessment, 2023)

Ambient air pollution and the health-related quality of life of older adults: Evidence from Shandong China - Jialong Tan; Nuo Chen; Jing Bai; Peizhe Yan; Xinyu Ma; Meiling Ren; Elizabeth Maitland; Stephen Nicholas; Wenjing Cheng; Xue Leng; Chen Chen; Jian Wang (Journal of Environmental Management, 2023)

Eco-friendly waterborne superhydrophobic/superoleophilic FEVE composite coating with prolonged mechanochemical and anti-scaling properties - Zhanjian Liu; Lina Ren; Baoshuang Zhang; Jing Jing; Xiguang Zhang; Meiling Li; Yuxin Fu; Huaiyuan Wang (Chemical Engineering Journal, 2023)

Correction to: Construction of HAnW‑based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

Construction of HAnW-based nanotwigs for removing inorganic fluorion in wastewater - Meiling Zhou; Hua Yang; Zejun Wang; Jiarui Ren; Rongmin Wang; Yufeng He (Environmental Science and Pollution Research, 2022)

First detection of the occurrence and study of the genetic diversity of novel putative kirkoviruses in donkey in China - Panpan Tong; Haifeng Deng; Liya Duan; Meiling Ren; Xiaozhen Song; Hao Wang; Duishanbayi Gulimire; Ling Kuang; Jinxin Xie (Virus Genes, 2022)

Study on the Law of Earth’s Surface Movement on Ultra-Long Working Face - Peng Rui; Fang Meiling; Ren Ruile; Zhu Jianming; Zhao Qifeng; Ouyang Zhenhua (Geotechnical and Geological Engineering, 2022)

Identification and genomic characterization of emerging CRESS DNA viruses in thoroughbred horses in China - Panpan Tong; Meiling Ren; Xinlong Xu; Xiaozhen Song; Lei Zhang; Ling Kuang; Jinxin Xie (Virus Genes, 2021)

First detection and genetic characterization of equid herpesvirus 2, 4, and 5 in China - Jinxin Xie; Panpan Tong; Lei Zhang; Meiling Ren; Xiaozhen Song; Chenyang Jia; Nuerlan Palidan; Li Zhang; Ling Kuang (Archives of Virology, 2021)

Safety Analysis Control Measures of Multiple Mining Soft Rock Roadways - Rui Peng; Meiling Fang; Ruile Ren; Qifeng Zhao; Hanwen Jia (Geotechnical and Geological Engineering, 2021)

The inhibition of miR-17-5p promotes cortical neuron neurite growth via STAT3/GAP-43 pathway - Liang Zhang; Zhijie Wang; Bo Li; Ziwei Xia; Xin Wang; Yucai Xiu; Zheng Zhang; Chuanjie Chen; Hong Song; Wenhua Li; Mei Yu; Meiling Zhang; et al. (Molecular Biology Reports, 2020)

Genome-wide investigation of microsatellite polymorphism in coding region of the giant panda (Ailuropoda melanoleuca) genome: a resource for study of phenotype diversity and abnormal traits - Meiling Cheng; Jianying Ren; Fujun Shen; Yan Huang; Zhenxin Fan; Megan Price; Bisong Yue; Xiuyue Zhang (Mammal Research, 2019)

Allelism analysis of BrRfp locus in different restorer lines and map-based cloning of a fertility restorer gene, BrRfp1, for pol CMS in Chinese cabbage (Brassica rapa L.) - Huamin Zhang; Junqing Wu; Zihui Dai; Meiling Qin; Lingyu Hao; Yanjing Ren; Qingfei Li; Lugang Zhang (Theoretical and Applied Genetics, 2017)